Flame retardant compositions, compounds, and methods of manufacture

By developing a composition containing isocyanate reactive compounds and foaming agents, the problem of providing mechanical stability and flame retardancy to the battery module while maintaining minimum weight is solved, achieving a high level of flame retardant performance and compressive strength.

CN119894955APending Publication Date: 2025-04-25HB FULLER CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380066335.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-26
Filing Date
2023-09-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The prior art is difficult to maintain the minimum weight requirement while providing mechanical stability and flame retardancy to battery modules.

Method used

A composition is developed including a first component of an isocyanate reactive compound and a foaming agent, and a second component of an isocyanate compound. The at least one component comprises at least 15% by weight of the first flame retardant component and after curing forms a foam compound with at least V2 grade flame retardancy as measured by the UL94 plastic flammability test.

Benefits of technology

It achieves mechanical stability and high-level flame retardant performance for battery modules without increasing weight, meeting the needs for flame retardant and compressive strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119894955A_ABST
    Figure CN119894955A_ABST
Patent Text Reader

Abstract

A composition configured to cure to form a foam compound that exhibits at least V2 class flame retardancy as measured by the UL 94 plastic flammability test when measured with a sample of the foam compound having a thickness no greater than 1 mm.
Need to check novelty before this filing date? Find Prior Art

Description

CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 63 / 377,139, filed on September 26, 2022, which is incorporated herein. Technical Field

[0001] The present disclosure relates to compositions and compounds having flame retardant properties. The present disclosure relates to compositions and compounds containing one or more flame retardants and suitable for potting electric cells in battery modules. background

[0002] Generally speaking, potting is the process of partially or completely filling a defined space within a housing with a material in order to maintain the objects within the housing in a spatial relationship relative to each other and to the housing. Potting can be used to provide resistance against shock and vibration. Certain compositions used for potting can be designed to establish a seal to protect against moisture, solvents, and corrosive agents.

[0003] The materials used to form the potting compound range in hardness from extremely soft to hard and rigid, and are designed to withstand a variety of environments. The compound used to pot the battery can be designed to provide mechanical stability and impact resistance, for example, to a battery module for a vehicle.

[0004] There is a need for compounds that provide mechanical stability to a contained object while adding minimal weight to the contained object. There is a need for compounds that are used in battery modules and provide flame retardancy. There is a need for compositions for forming flame retardant potting compounds used in battery modules. Overview

[0005] A composition is disclosed herein, comprising a first component comprising an isocyanate reactive compound and a blowing agent, and a second component comprising an isocyanate compound. At least one of the first component and the second component comprises a first flame retardant component of at least 15% by weight based on the gross weight of the composition. The composition is configured to solidify to form a foam compound (foam compound), which exhibits at least V2 grade flame retardancy measured by UL94 plastic flammability test when measured with a sample of a foam compound having a thickness of not more than 1.6 millimeters. In some aspects, the composition is configured to solidify to form a foam compound that exhibits at least V2 grade flame retardancy measured by UL 94 plastic flammability test when measured with a sample of a foam compound having a thickness of not more than 1 millimeter.

[0006] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the foam compound having a thickness of no greater than 1 mm.

[0007] In some aspects, the composition is configured to solidify to form a foam compound, which shows a compressive strength of at least 20psi when measured by a foam integrity test for a sample of a foam compound not more than 1 millimeter in thickness. In some aspects, the composition is configured to solidify to form a foam compound that shows a compressive strength of at least 30psi when measured by a foam integrity test for a sample of a foam compound not more than 1 millimeter in thickness. In some aspects, the composition is configured to solidify to form a foam compound that shows a compressive strength of at least 20psi when measured by a foam integrity test for a sample of a foam compound not more than 1.6 millimeters in thickness. In some aspects, the composition is configured to solidify to form a foam compound that shows a compressive strength of at least 20psi when measured by a foam integrity test for a sample of a foam compound not more than 2 millimeters in thickness. In some aspects, the composition is configured to solidify to form a foam compound that shows a compressive strength of at least 20psi when measured by a foam integrity test for a sample of a foam compound not more than 3 millimeters in thickness.

[0008] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 6.5 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 2 mm.

[0009] In some aspects, the first component has a viscosity of greater than 1 to less than 5500 cP, and wherein the second component has a viscosity of greater than 1 to less than 1000 cP, all at a temperature of 25°C to 35°C. In some aspects, the composition further comprises a second flame retardant component. In some aspects, the composition further comprises a second flame retardant component containing non-halogenated expandable graphite. In some aspects, the composition further comprises a second flame retardant component in both the first component and the second component. In some aspects, the composition further comprises a second flame retardant component of at least 1% by weight based on the total weight of the composition.

[0010] In some aspects, the composition further comprises at least 1 wt % to 14 wt % of a second flame retardant component based on the total weight of the composition. In some aspects, the first component, the second component, the first flame retardant component, and the second flame retardant component are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RVF viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of about 25°C.

[0011] In some aspects, the composition comprises at least 20 wt % of the first flame retardant component based on the total weight of the composition. In some aspects, the composition comprises greater than 25 wt % of the first flame retardant component based on the total weight of the composition. In some aspects, the composition comprises at least 30 wt % of the first flame retardant component based on the total weight of the composition.

[0012] In some aspects, the first flame retardant component includes a phosphate ester. In some aspects, the first component includes an isocyanate reactive compound with a functionality of three or more. In some aspects, the isocyanate reactive compound is a polyol. In some aspects, the isocyanate reactive compound includes at least one polyether polyol. In some aspects, the isocyanate compound includes MDI. In some aspects, the isocyanate compound includes polymeric MDI.

[0013] In some aspects, the first flame retardant component has a viscosity of no greater than 300 cP at a temperature of 25° C. to 35° C. In some aspects, the first flame retardant component exhibits a viscosity of about 10 cP to about 2000 cP at a temperature of 25° C. to 35° C. In some aspects, the composition is configured to cure to form a 3 The density of the foam compound.

[0014] In some aspects, the first component includes 20 wt % to 40 wt % polyol, 20 wt % to 50 wt % phosphate flame retardant component and 0.4 wt % to 2.0 wt % blowing agent, all based on the total weight of the first component; the second component includes 10 wt % to 90 wt % MDI and 10 wt % to 90 wt % phosphate flame retardant component, all based on the total weight of the second component, and at least one of the first component and the second component includes 1 wt % to 14 wt % of the second flame retardant component based on the total weight of the composition.

[0015] In some aspects, when measured with a Brookfield RVF viscometer at a spindle speed of 50 rpm at a temperature of 25°C to 35°C, at least one of the following (a) and (b) is exhibited: (a) the first component has a viscosity greater than 1 to less than 5500 cP, (b) the second component has a viscosity greater than 1 to less than 1000 cP.

[0016] Disclosed herein is a composition comprising a first component comprising an isocyanate reactive compound and a blowing agent; a second component comprising an isocyanate compound; and at least one of the first component and the second component comprises at least 15 weight percent of a first flame retardant component that is liquid at a temperature of 25°C to 35°C, based on the total weight of the composition. At least one of the first component and the second component comprises at least 1 weight percent of a second flame retardant component comprising expandable graphite, based on the total weight of the composition. The first component, the second component, the first flame retardant, and the second flame retardant are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RV viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of approximately 25°C.

[0017] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm.

[0018] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 1 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 6.5 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 2 mm.

[0019] In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 1 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 1.6 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 2 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 3 mm.

[0020] In some aspects, the first component has a viscosity of greater than 1 to less than 5500 cP, and wherein the second component has a viscosity of greater than 1 to less than 1000 cP, all at a temperature of 25° C. to 35° C. In some aspects, the first component, the second component, the first flame retardant, and the second flame retardant are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RV viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of about 25° C. In some aspects, the first and second flame retardant components are present in both the first component and the second component.

[0021] In some aspects, the second flame retardant is a non-halogenated expandable graphite. In some aspects, the first flame retardant component includes a phosphate ester. In some aspects, the composition comprises at least 20% by weight of the first flame retardant component based on the total weight of the composition. In some aspects, the composition comprises greater than 25% by weight of the first flame retardant component based on the total weight of the composition. In some aspects, the composition comprises at least 30% by weight of the first flame retardant component based on the total weight of the composition.

[0022] In some aspects, the first component includes an isocyanate-reactive compound having a functionality of 3 or more. In some aspects, the isocyanate-reactive compound is a polyol. In some aspects, the isocyanate-reactive compound includes at least one polyether polyol. In some aspects, the isocyanate compound includes MDI. In some aspects, the isocyanate compound includes polymeric MDI.

[0023] In some aspects, the first component includes 20 wt % to 40 wt % polyol; 20 wt % to 50 wt % phosphate ester flame retardant; and 0.4 wt % to 2.0 wt % blowing agent, all based on the total weight of the first component; the second component includes 10 wt % to 90 wt % MDI; and 10 wt % to 90 wt % phosphate ester flame retardant; all based on the total weight of the second component, and at least one of the first component and the second component includes 1 wt % to 14 wt % of the second flame retardant based on the total weight of the composition.

[0024] In some aspects, the first flame retardant component has a viscosity of no greater than 300 cP at a temperature of 25° C. to 35° C. In some aspects, the first flame retardant component exhibits a viscosity of about 200 cP to about 2000 cP at a temperature of 25° C. to 35° C. In some aspects, the composition is configured to cure to form a 3 The density of the foam compound.

[0025] In some aspects, when measured with a Brookfield RVF viscometer at a spindle speed of 50 rpm at a temperature of 25°C to 35°C, at least one of the following (a) and (b) is exhibited: (a) the first component has a viscosity greater than 1 to less than 5500 cP, (b) the second component has a viscosity greater than 1 to less than 1000 cP.

[0026] Disclosed herein is a composition comprising a first component comprising an isocyanate reactive compound and a blowing agent; a second component comprising an isocyanate compound. At least one of the first component and the second component comprises at least 15 wt % of a first flame retardant component that is liquid at a temperature of 25°C to 35°C, based on the total weight of the composition; and at least one of the first component and the second component comprises at least 1 wt % of a second flame retardant comprising expandable graphite, based on the total weight of the composition. When measured with a Brookfield RVF viscometer at a spindle speed of 50 rpm at a temperature of 25°C to 35°C, at least one of the following (a) and (b) is exhibited: (a) the first component has a viscosity of greater than 1 to less than 5500 cP, (b) the second component has a viscosity of greater than 1 to less than 1000 cP.

[0027] In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 1 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 1.6 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 2 mm. In some aspects, the composition is configured to solidify to form a foam compound that exhibits a compressive strength of at least 20 psi when measured with a foam integrity test for a sample of a foam compound having a thickness of no more than 3 mm.

[0028] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm.

[0029] In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 1 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 6.5 mm. In some aspects, the composition is configured to cure to form a foam compound that exhibits at least V0 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no more than 2 mm.

[0030] In some aspects, the second flame retardant comprises non-halogenated expandable graphite. In some aspects, the second flame retardant is present in both the first component and the second component. In some aspects, the composition comprises at least 1 wt % to 14 wt % of the second flame retardant component based on the total weight of the composition.

[0031] Disclosed herein is a composition comprising a first component comprising an isocyanate reactive compound and a blowing agent, and a second component comprising an isocyanate compound. At least one of the first component and the second component comprises at least 15 weight percent of a first flame retardant component based on the total weight of the composition. The composition is configured to cure to form a foam compound that exhibits a compressive strength of at least 20 psi when measured using a foam integrity test on a sample of the foam compound having a thickness of no greater than 1 mm.

[0032] In some aspects, the composition is configured to solidify and form a foam compound that exhibits at least V1 flame retardancy measured by UL 94 plastic flammability test when tested with a sample of a foam compound having a thickness of not more than 1 mm. In some aspects, the composition is configured to solidify and form a foam compound that exhibits at least 20psi compressive strength when measured with a foam integrity test for a sample of a foam compound having a thickness of not more than 1.6 mm. In some aspects, the composition is configured to solidify and form a foam compound that exhibits at least 20psi compressive strength when measured with a foam integrity test for a sample of a foam compound having a thickness of not more than 2 mm. In some aspects, the composition is configured to solidify and form a foam compound that exhibits at least 20psi compressive strength when measured with a foam integrity test for a sample of a foam compound having a thickness of not more than 3 mm. In some aspects, the composition is configured to solidify and form a foam compound that exhibits at least V0 flame retardancy measured by UL 94 plastic flammability test when tested with a sample of a foam compound having a thickness of not more than 1 mm. In some aspects, the composition comprises a second flame retardant containing non-halogenated expandable graphite. In some aspects, the second flame retardant is present in both the first component and the second component. In some aspects, the composition comprises at least 1 wt % to 14 wt % of the second flame retardant component based on the total weight of the composition.

[0033] Disclosed herein is a compound comprising a foamed compound having a thickness of less than 0.60 g / cm 3 The foam compound has a density of , and when tested with a sample of the foam compound having a thickness of no more than 1 mm, the foam compound exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test. In some aspects, when tested with a sample of the foam compound having a thickness of no more than 1 mm, the foam compound exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test. In some aspects, when tested with a sample of the foam compound having a thickness of no more than 1 mm, the foam compound exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test.

[0034] In some aspects, the compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 2 mm. In some aspects, the compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 3 mm.

[0035] In some aspects, the foam compound is at least one of a polyurethane foam compound, a silicone foam compound, and an epoxy-based foam compound.

[0036] In some aspects, the compound exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1 mm. In some aspects, the compound exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1 mm. In some aspects, the compound exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1 mm.

[0037] In some aspects, the compound exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1.6 mm. In some aspects, the compound exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1.6 mm. In some aspects, the compound exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 1.6 mm.

[0038] In some aspects, the compound exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 2 mm. In some aspects, the compound exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 2 mm. In some aspects, the compound exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the compound having a thickness of no greater than 2 mm.

[0039] In some aspects, the compound includes a liquid flame retardant component in an amount of at least 15% by weight based on the total weight of the compound. In some aspects, the compound includes a liquid flame retardant component in an amount of at least 20% by weight based on the total weight of the compound. In some aspects, the compound includes a liquid flame retardant component in an amount of at least 25% by weight based on the total weight of the compound. In some aspects, the compound includes a liquid flame retardant component in an amount of at least 30% by weight based on the total weight of the compound.

[0040] In some aspects, the compound includes an expanded graphite flame retardant component in an amount of at least 1% by weight based on the total weight of the compound. In some aspects, the compound includes an expanded graphite flame retardant component in an amount of at least 2% by weight based on the total weight of the compound. In some aspects, the compound includes an expanded graphite flame retardant component in an amount of at least 5% by weight based on the total weight of the compound. In some aspects, the compound includes an expanded graphite flame retardant component in an amount of at least 7% by weight based on the total weight of the compound.

[0041] In some aspects, the compound is derived from a composition comprising a first component comprising an isocyanate reactive compound and a blowing agent and a second component comprising an isocyanate compound, at least 15% by weight of a first flame retardant component that is liquid at a temperature of 25°C to 35°C, based on the total weight of the composition; and at least 1% by weight of a second flame retardant comprising expandable graphite, based on the total weight of the composition. The first component, the second component, the first flame retardant, and the second flame retardant are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RVF viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of about 25°C.

[0042] A battery module is disclosed herein, comprising a first battery encapsulated in a foamed compound. The foamed compound has a viscosity of less than 0.60 g / cm 3 The foam compound has a density of less than 0.60 g / cm and exhibits at least a V2 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no greater than 1 mm. 3 The foam compound has a density of less than 0.60 g / cm and exhibits at least a V1 flame retardancy as measured by the UL 94 plastic flammability test when tested with a sample of the foam compound having a thickness of no greater than 1 mm. 3 The foam compound has a density of and exhibits at least V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm.

[0043] In some aspects, when tested with a sample of the foam compound having a thickness of no more than 2 mm, the foam compound exhibits at least a V2 flame retardancy as measured by the UL 94 plastic flammability test. In some aspects, when tested with a sample of the foam compound having a thickness of no more than 2 mm, the foam compound exhibits at least a V1 flame retardancy as measured by the UL 94 plastic flammability test. In some aspects, when tested with a sample of the foam compound having a thickness of no more than 2 mm, the foam compound exhibits at least a V0 flame retardancy as measured by the UL 94 plastic flammability test. In some aspects, when tested with a sample of the foam compound having a thickness of no more than 6.5 mm, the foam compound exhibits at least a V1 flame retardancy as measured by the UL 94 plastic flammability test.

[0044] In some aspects, the foam compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the foam compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 2 mm. In some aspects, the foam compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 3 mm.

[0045] In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 15% by weight based on the total weight of the compound. In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 20% by weight based on the total weight of the compound. In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 25% by weight based on the total weight of the compound. In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 30% by weight based on the total weight of the compound.

[0046] In some aspects, the foam compound includes an expanded graphite flame retardant component in an amount of at least 1% by weight based on the total weight of the compound. In some aspects, the foam compound includes an expanded graphite flame retardant component in an amount of at least 2% by weight based on the total weight of the compound. In some aspects, the foam compound includes an expanded graphite flame retardant component in an amount of at least 5% by weight based on the total weight of the compound. In some aspects, the foam compound includes an expanded graphite flame retardant component in an amount of at least 7% by weight based on the total weight of the compound.

[0047] In some aspects, the foam compound is at least one of a polyurethane foam compound, a silicone foam compound, and an epoxy foam compound. In some aspects, the foam compound is derived from a first component comprising an isocyanate reactive compound and a blowing agent; a second component comprising an isocyanate compound; at least 15% by weight of a first flame retardant component that is liquid at a temperature of 25°C to 35°C based on the total weight of the composition; and at least 1% by weight of a second flame retardant comprising expandable graphite based on the total weight of the composition. The first component, the second component, the first flame retardant, and the second flame retardant are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RVF viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of approximately 25°C.

[0048] A battery module is disclosed herein, comprising a foam composition and an electric cell embedded in the composition, wherein the foam composition comprises a liquid flame retardant component in an amount of at least 15 wt % based on the total weight of the composition and a second flame retardant comprising expandable graphite in an amount of at least 1 wt % based on the total weight of the composition.

[0049] In some aspects, the foam compound exhibits a compressive strength of at least 20 psi when measured using a foam integrity test on a sample of the foam compound having a thickness of no greater than 1 mm. In some aspects, the battery module includes a plurality of cells, each cell having a bottom, a top, and a length defined therebetween, the compound being at a substantially level height.

[0050] In some aspects, when tested with a sample of the polyurethane foam compound having a thickness of no greater than 1 mm, the foam compound exhibits at least a V1 flame retardancy as measured by the UL 94 Plastics Flammability Test. In some aspects, when tested with a sample of the polyurethane foam compound having a thickness of no greater than 1 mm, the foam compound exhibits at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test.

[0051] In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 20% by weight based on the total weight of the compound. In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 25% by weight based on the total weight of the compound. In some aspects, the foam compound includes a liquid flame retardant component in an amount of at least 30% by weight based on the total weight of the compound. In some aspects, the foam compound includes a second flame retardant component in an amount of at least 2% by weight based on the total weight of the compound. In some aspects, the foam compound includes a second flame retardant component in an amount of at least 3% by weight based on the total weight of the compound.

[0052] In some aspects, the foam composition includes the second flame retardant component in an amount of at least 5 weight percent, based on the total weight of the composition.

[0053] Although multiple embodiments are disclosed, other embodiments of the present disclosure will be apparent to those skilled in the art from the following detailed description, which shows and describes exemplary embodiments of the present disclosure. Therefore, the drawings and detailed description should be regarded as illustrative rather than restrictive. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 is a perspective view of a battery module according to certain embodiments.

[0055] Figure 2 is a top view of a battery module according to certain embodiments.

[0056] Figure 3 is a front view of a battery module according to certain embodiments.

[0057] Figure 4 is a perspective view of a battery module according to certain embodiments.

[0058] Figure 5 is a top view of a battery module according to certain embodiments.

[0059] Figure 6 is an exploded view of a battery module according to certain embodiments. definition

[0060] As used herein, a potting compound is defined as a solid material used to embed an object in a container and maintain the object in a spatial relationship with the container.

[0061] As used herein, a potting composition is defined as a liquid composition suitable for curing to form a potting compound.

[0062] As used herein, room temperature is defined as a temperature between 22°C and 25°C.

[0063] As used herein, foam is defined as a material formed from a bulk component defining voids throughout the material.

[0064] As used herein, self-leveling is defined as exhibiting the property of being able to flow to form a level surface without the application of external forces other than gravity. Details

[0065] Disclosed herein is a compound having flame retardant properties, the flame retardant properties being measured with a sample of the compound having a size of at least 150 mm long x 13 mm wide and a thickness of no more than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even 1.0 mm. The compound has at least a V2 flame retardancy as measured by the UL 94 plastic flammability test, as measured with a strip of the sample compound having a size of at least 150 mm long x 13 mm wide and a thickness of no more than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even 1.0 mm. In some embodiments, the compound has at least a V1 flame retardancy as measured by the UL 94 plastic flammability test, as measured with a strip of the sample compound having a size of at least 150 mm long x 13 mm wide and a thickness of no more than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even 1.0 mm. In some embodiments, the compound has a flame retardancy of at least V0 as measured by the UL 94 Plastics Flammability Test, as measured using a strip of sample compound at least 150 mm long by 13 mm wide and no thicker than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even no thicker than 1.0 mm.

[0066] Disclosed herein is a compound having flame retardant properties and a density of no greater than 0.6 grams per cubic centimeter (g / cc), no greater than 0.5 g / cc, no greater than 0.4 g / cc, no greater than 0.3 g / cc, no greater than 0.2 g / cc, no greater than 0.18 g / cc, no greater than 0.16 g / cc, no greater than 0.14 g / cc, no greater than 1.2 g / cc, no greater than 1.0 g / cc, or even no greater than 0.05 g / cc.

[0067] Disclosed herein is a composition suitable for forming a compound of low density and having flame retardant properties.Disclosed herein is a composition suitable for forming a flame retardant foam compound.Disclosed herein is a composition suitable for forming a compound of low density, flame retardant, and exhibiting a compressive strength of at least 20 psi, at least 25 psi, at least 30 psi, at least 40 psi, at least 50 psi, at least 60 psi, at least 70 psi, or even at least 75 psi after being subjected to the foam integrity test disclosed herein. Composition

[0068] In some embodiments, the composition can be a one-part composition. In some embodiments, the composition can be a two-part composition. In some embodiments, the composition can be a one-part composition containing at least a first flame retardant composition. In some embodiments, the composition can be a two-part composition formed by a first component reacting with a second component. At least one of the first component or the second component contains a first flame retardant component.

[0069] In some embodiments, the composition may include silicone, epoxy resin, such as a one-component or two-component epoxy resin, a bio-based component or polyurethane. In some embodiments, the first component and the second component may be selected to form a thermoplastic polyurethane component (TPU). The composition may be a liquid that solidifies to form a solid compound. The composition may be positioned when in a liquid phase, and flows around an object and through the space defined between adjacent objects, and then solidifies to form a solid compound. The composition may have sufficient fluidity before solidification to pour as a liquid, and it may flow around an object and be stabilized at a level height (level height) around the object. The composition may be self-leveling (self-leveling).

[0070] In some embodiments, the composition exhibits a relative humidity of no greater than 100 centipoise (cP); 200 cP; 300 cP; 400 cP; 500 cP; 600 cP; 700 cP; 800 cP; 900 cP; 1,000 cP; 1,100 cP; 1,200 cP; 1,300 cP; 1,400 cP; 1,500 cP; 2,000 cP; or about 100,000 cP. Component 1

[0071] The first component is a liquid at room temperature. In some embodiments, the first component has a viscosity of greater than 1 to less than 100,000 cP at room temperature. In some embodiments, the first component has a viscosity of no greater than 100,000 cP; 40,000; 30,000; 20,000; 10,000 cP; 9,000 cP; 8,000 cP; 7,000 cP; 6,000 cP; 5,500 cP; 5,000 cP; 4,500 cP; 4000 cP; 3,500 cP; 3 cP; or even a viscosity not greater than 100 cP.

[0072] In some embodiments, the first component has a pH of approximately 100 cP; 200 cP; 300 cP; 400 cP; 500 cP; 600 cP; 700 cP; 800 cP; 900 cP; 1,000 cP; 1,100 cP; 1,200 cP; 1,300 cP; 1,400 cP; 1,500 cP; 2,000 cP; 2,500 cP; 3,0 or about 100,000 cP, or a viscosity between any pair of the foregoing values.

[0073] In some embodiments, the first component includes one or more isocyanate reactive compounds. The isocyanate reactive compound can be a compound containing active hydrogen, such as an amine, an alcohol or a thiol. The first component can include an isocyanate reactive compound with a functionality of 2 or more. Preferred isocyanate reactive compounds can be those with a functionality of 3 or more.

[0074] Suitable isocyanate-reactive compounds are those which are liquid at room temperature. Preferred isocyanate-reactive compounds are those which have a low viscosity at room temperature.

[0075] In some embodiments, suitable isocyanate-reactive compounds have a viscosity at room temperature of no greater than 10,000 cP; 9,000 cP; 8,000 cP; 7,000 cP; 6,000 cP; 5,500 cP; 5,000 cP; 4,500 cP; 4000 cP; 3,500 cP; 3,000 cP; 2,500 cP; 2,000 cP; 1,500 cP; 1,400 cP; 1,300 cP; 1,200 cP; 1,100 cP; 1,000 cP; 900 cP; 800 cP; 700 cP; 600 cP; 500 cP; 400 cP; 300 cP; 200 cP; or even no greater than 100 cP.

[0076] In some embodiments, suitable isocyanate-reactive compounds may have a viscosity at room temperature of about 100 cP; 200 cP; 300 cP; 400 cP; 500 cP; 600 cP; 700 cP; 800 cP; 900 cP; 1,000 cP; 1,100 cP; 1,200 cP; 1,300 cP; 1,400 cP; 1,500 cP; 2,000 cP; 2,500 cP; 3,000 cP; 3,500 cP; 4000 cP; or 4,500 cP; to about 5,000 cP; 5,500 cP; 6,000 cP; about 10,000; about 20,000; about 30,000; about 40,000; or about 100,000; or a viscosity between any pair of the foregoing values.

[0077] In some embodiments, the isocyanate-reactive compound can be a polyol. The isocyanate-reactive compound can be a combination of two or more polyols. For example, the isocyanate-reactive compound can be a diol polyol, a triol polyol, a tetraol polyol or a higher polyol, and a combination thereof. Preferred examples of the polyol that can be used as the isocyanate-reactive compound include those with low viscosity at room temperature.

[0078] In some embodiments, suitable polyols may include polyhydroxy ethers, including substituted or unsubstituted polyalkylene ether glycols or polyhydroxy polyalkylene ethers; polyhydroxy polyesters; ethylene oxide or propylene oxide adducts of monosubstituted esters of polyols and glycerol; polymer polyols, such as graft polyols containing a certain proportion of (e.g., in situ polymerizable) vinyl monomers; and mixtures and combinations thereof. Further examples of suitable polyols include poly (diethylene glycol adipate).

[0079] In some embodiments, homopolymers and copolymers of polyoxyalkylenes can be used. In some embodiments, the copolymer of polyoxyalkylene polyols may include at least one compound including ethylene glycol, propylene glycol, diethylene glycol, dipropylene glycol, triethylene glycol, 2-ethylhexanediol-1,3-glycerol, 1,2,6-hexanetriol, trimethylolpropane, trimethylolethane, tri(hydroxyphenyl)propane, triethanolamine, triisopropanolamine; and a compound including ethylene oxide, propylene oxide and butylene oxide, adducts.

[0080] The polyol may be selected from polyether polyols and polyester polyols. Suitable polyether polyols may include, but are not limited to, polyoxyalkylene polyols such as polyethylene glycol, polypropylene glycol, polytetramethylene glycol, polybutylene glycol, and mixtures and combinations thereof. In some embodiments, suitable polyether polyols may have a number average molecular weight (M) of less than 10,000; 9,000; 8,000; 7,000; 6,000; 5,000; 4,000; 3,000; 2,000; 1,000 or even less than 900, 800, 700, 600, 500, 400, 300, 200 or less than 100. n In some embodiments, suitable polyether polyols may have a number average molecular weight (M) of 100, about 200, about 300, about 400, about 600, to about 800, about 1,000, about 4,000, about 6,000, about 7,000, or about 10,000. n ), or a molecular weight between any pair of the above values.

[0081] In some embodiments, suitable polyester polyols may be formed by the reaction of one or more polyols having from about 2 to about 15 carbon atoms with one or more polycarboxylic acids having from about 2 to about 14 carbon atoms. Examples of suitable polyols include ethylene glycol, propylene glycol such as 1,2-propylene glycol, 1,3-propylene glycol, glycerol, pentaerythritol, trimethylolpropane, 1,4,6-octantriol, butanediol, pentanediol, hexanediol, dodecanediol, octanediol, chloropentanediol, glycerol monoallyl ether, glycerol monoethyl ether, diethylene glycol, 2-ethylhexanediol, 1,4-cyclohexanediol, 1,2,6-hexanetriol, 1,3,5-hexanetriol, 1,3-bis-(2-hydroxyethoxy)propane, and similar components.

[0082] In some embodiments, the isocyanate-reactive compound is present in the first component at a weight percentage of about 20%, about 30%, or about 40%, to about 70%, about 80%, about 90%, or about 100%, based on the total weight of the first component, or a weight percentage between any pair of the above values. In some embodiments, the isocyanate-reactive compound is present in the first component at a weight percentage of at least 20%, 25%, 30%, 35%, 40%, 45%, or at least 50%, based on the total weight of the first component. In embodiments having more than one isocyanate-reactive compound, the total amount of all isocyanate-reactive compounds present in the first component has a combined weight percentage of about 20%, about 30%, or about 40%, to about 70%, about 80%, about 90%, or about 100%, based on the total weight of the first component, or a weight percentage between any pair of the above values.

[0083] Suitable commercially available polyols that can be used include triol polyether polyols available under the trade name POLY-G 30-240 or POLY-G 30-238 (available from Monument Chemical Group, Brandenburg, KY, USA), triol polyether polyols available under the trade name VORANOL 230-238 (available from Dow Chemical Company, Midland, MI, USA), and polyether polyols sold under the trade name ARCOL LHT-240 (available from Covestro AG, Leverkusen, Germany). Second component

[0084] In embodiments containing a second component, the second component is a liquid at room temperature. The second component has a viscosity of less than 100,000 cP at room temperature. In some embodiments, the second component has a viscosity of about 100 cP; 200 cP; 300 cP; 400 cP; 500 cP; 600 cP; 700 cP; 800 cP; 900 cP; 1,000 cP; 1,100 cP; 1,200 cP; 1,300 cP; 1,400 cP; 1,500 cP; 2,000 cP; 2,500 cP; 3,000 cP; 3,500 cP; 4000 cP; or 4,500 cP; to about 5,000 cP; 5,500 cP; 6,000 cP; about 10,000; about 20,000; about 30,000; about 40,000; or about 100,000, or a viscosity between any pair of the foregoing values. In some embodiments, the second component has a viscosity at room temperature of no greater than 2,000 cP; 1,500 cP; 1,000 cP; 800 cP; 600 cP; 400 cP; 200 cP or even no greater than 100 cP.

[0085] The second component may include an isocyanate compound. The isocyanate compound may have an average isocyanate functionality of 2 or more. In some embodiments, suitable isocyanate compounds include those that exhibit a viscosity of no greater than 2,000 cP; 1,500 cP; 1,000 cP; 800 cP; 600 cP; 400 cP; 200 cP or even no greater than 100 cP at room temperature.

[0086] In some embodiments, the isocyanate compound can be a monomer. In some embodiments, the isocyanate compound can be a polymer. In some embodiments, the isocyanate compound can be a prepolymer. For example, the isocyanate compound can be a polymer reacted with the second isocyanate compound, such as an isocyanate-terminated oligomer. In some embodiments, the isocyanate compound can be a polymeric isocyanate.

[0087] In some embodiments, suitable isocyanate compounds have a viscosity at room temperature of no greater than 10,000 cP; 9,000 cP; 8,000 cP; 7,000 cP; 6,000 cP; 5,500 cP; 5,000 cP; 4,500 cP; 4000 cP; 3,500 cP; 3,000 cP; 2,500 cP; 2,000 cP; 1,500 cP; 1,400 cP; 1,300 cP; 1,200 cP; 1,100 cP; 1,000 cP; 900 cP; 800 cP; 700 cP; 600 cP; 500 cP; 400 cP; 300 cP; 200 cP; or even no greater than 100 cP. For example, suitable polymeric isocyanates have a viscosity at room temperature of no greater than 10,000 cP; 9,000 cP; 8,000 cP; 7,000 cP; 6,000 cP; 5,500 cP; 5,000 cP; 4,500 cP; 4000 cP; 3,500 cP; 3,000 cP; 2,500 cP; 2,000 cP; 1,500 cP; 1,400 cP; 1,300 cP; 1,200 cP; 1,100 cP; 1,000 cP; 900 cP; 800 cP; 700 cP; 600 cP; 500 cP; 400 cP; 300 cP; 200 cP; or even no greater than 100 cP.

[0088] Suitable isocyanate compounds include, but are not limited to, aromatic isocyanates, such as aromatic diisocyanates, or aliphatic isocyanates, such as aliphatic diisocyanates. In some embodiments, the isocyanate compound has 1 to 10 aliphatic or aromatic groups substituted with isocyanate groups.

[0089] Suitable isocyanate compounds include methylene diphenyl isocyanate compounds such as diphenylmethane diisocyanate (including isomers thereof), methylene diphenyl diisocyanate (MDI), carbodiimide-modified MDI, hydrogenated diphenylmethane isocyanate (HMDI), hexamethylene diisocyanate (HDI), isophorone diisocyanate (IPDI), polymeric diphenylmethane isocyanate, diphenylmethane-4,4'-diisocyanate, diphenylmethane-2,2'-diisocyanate, diphenylmethane-2,4'-diisocyanate and other oligomeric methylene isocyanates; toluene diisocyanate compounds (TDI) (including isomers thereof), tetramethylxylene diisocyanate (TMXDI), isomers of naphthalene diisocyanate, isomers of triphenylmethane triisocyanate, and mixtures and combinations thereof. In some cases, aliphatic diisocyanates, triisocyanates, and polyisocyanates are also suitable isocyanate compounds, including, for example, hydrogenated aromatic diisocyanates, aliphatic polyisocyanates, or alicyclic polyisocyanates.

[0090] Suitable commercially available isocyanate compounds include modified liquid MDI sold under the trade name ISONATE 143L (available from The Dow Chemical Company, Midland, MI, USA) and polymeric MDI sold under the trade name RUBINATE M (available from Huntsman Corporation, The Woodlands, TX, USA).

[0091] In some embodiments, the isocyanate compound is present in the second component at a weight percentage of about 20%, about 30% or about 40%, to about 70%, about 80%, about 90% or about 100%, based on the total weight of the second component, or a weight percentage between any pair of the above values. In some embodiments, the isocyanate compound is present in the second component at a weight percentage of at least 50%, 55%, 60%, 70%, 75%, 80%, at least 85%, at least 90%, based on the total weight of the second component. In embodiments with more than one isocyanate compound, the total amount of all isocyanate compounds present in the second component has a combined weight percentage of about 20%, about 30% or about 40%, to about 70%, about 80%, about 90% or about 100%, based on the total weight of the second component, or a weight percentage between any pair of the above values. Foaming agent

[0092] In some embodiments, the composition includes a blowing agent. In some embodiments, the blowing agent can be a gas. In some embodiments, the blowing agent can be a liquid.

[0093] For example, a blowing agent can be a gas that is injected into the composition to create voids, such as pockets of gas, in the composition once the composition is to be dispensed, such as when the components of the composition are mixed. Suitable blowing agents that can be injected into the composition include nitrogen, pentanes (e.g., cyclopentane and isopentane), and carbon dioxide.

[0094] In some embodiments, suitable blowing agents are those that can react with the remaining components of the composition to produce voids, such as air pockets. For example, useful blowing agents can react with the remaining components of the composition to form voids, such as bubbles or cavities defined by the composition.

[0095] Chemical blowing agents may include water, azodicarbonamide (eg, for vinyl), hydrazine and other nitrogen-based materials (for thermoplastic and elastomeric foams), and sodium bicarbonate (for thermoplastic foams).

[0096] In some embodiments, the blowing agent is water. For example, for a compound to be formed from a polyurethane, water may be included to react with the components that form the polyurethane to form carbon dioxide gas when the polyurethane components are mixed. The carbon dioxide gas forms bubbles in the liquid composition. The bubbles form cavities in the polyurethane after curing and hardening to obtain a foamed compound.

[0097] In some embodiments, the blowing agent can be included in the first component. For example, in some embodiments, the blowing agent can be a liquid blowing agent included in the first component.

[0098] In some embodiments, the blowing agent is present in the composition at a weight percent of greater than 0, about 0.1%, about 0.5%, or about 1.0%, to about 1.5%, about 2.0%, about 2.5%, about 3.0%, about 4.0%, or between any pair of the foregoing values, based on the total weight of the first component.

[0099] In some embodiments, low density compounds can be formed with compositions including microballoons, such as expanded or unexpanded balls, such as syntactic foams. For example, solid particles formed from glass or polymeric materials can be used to form three-dimensional shapes, such as beads or bubbles, that define a center of gas-filled material. The beads or bubbles can be distributed throughout a bulk substance that can solidify and trap the beads or bubbles, thereby reducing the overall density of the solidified material. First flame retardant component

[0100] The composition includes at least one first flame retardant component. The first flame retardant component is preferably liquid at room temperature. In the composition formed by the first component and the second component, the flame retardant component can be present in one or both of the first component and the second component. In some embodiments, in the composition formed by the first component and the second component, the flame retardant component can be added to the composition in which the first component and the second component are combined.

[0101] In some embodiments, suitable flame retardant components exhibit a viscosity of no greater than 2,000 cP; 1,500 cP; 1,000 cP; 800 cP; 600 cP; 400 cP; 200 cP; or even no greater than 100 cP at room temperature. Suitable first flame retardant components include those having a viscosity of about 30 cP, about 40 cP, about 100 cP, about 200 cP, about 300 cP, or about 400 cP, to about 600 cP, about 700 cP, about 800 cP, or about 900 cP, or about 2000 cP at room temperature, or a viscosity between any pair of the above values.

[0102] In some embodiments, preferred liquid flame retardant components include those having a viscosity of no greater than about 300 cP at room temperature. For example, preferred liquid flame retardant components include those having a viscosity of about 40, about 60, or about 80 or about 100, to about 150, about 200, about 250 or about 300 at room temperature, or a viscosity between any pair of the above values.

[0103] In some embodiments, the first flame retardant component can be a non-halogenated flame retardant. In some embodiments, the first flame retardant component can be a halogenated flame retardant.

[0104] In some embodiments, the first flame retardant component includes a phosphate. The first flame retardant component may include a non-halogenated phosphate. The first flame retardant component may include a halogenated phosphate. The first flame retardant component may include one or both of a brominated phosphate and a chlorinated phosphate. For example, a suitable liquid flame retardant that can be used as the first flame retardant may be tris (2-chloroisopropyl) phosphate. The first flame retardant component may include a liquid phosphorous polyol.

[0105] The first flame retardant component may include one or more brominated organic compounds, including brominated diols, brominated monoalcohols, brominated ethers, brominated phosphates, and combinations thereof. Brominated organic compounds suitable as the first flame retardant component include tetrabromobisphenol-A, hexabromocyclododecane, poly(pentabromobenzyl acrylate), pentabromobenzyl acrylate, tetrabromobisphenol A-bis(2,3-dibromopropyl ether), tribromophenol, dibromoneopentyl glycol, tribromoneopentyl alcohol, tris(tribromoneopentyl)phosphate, and 4,4'-isopropylidenebis[2-(2,6-dibromophenoxy)ethanol], and combinations thereof.

[0106] In some embodiments, suitable commercially available flame retardants that may be included as the first flame retardant component are phosphate ester flame retardants available under the trade name FYROL A710, non-halogenated phosphate ester flame retardants available under the trade name FYROLFLEX RDP, chlorinated phosphate esters available under the trade name FYROL PCF, butylated triphenyl phosphate available under the trade name PHOSFLEX 71B (all available from ICL Industrial Products, St. Louis, MO, USA); brominated flame retardant (ethylene bistetrabromophthalimide) available under the trade name SAYTEX BT-93 (from Albemarle Corporation, Baton Rouge, LA, USA); phosphorus flame retardant (isopropylated triaryl phosphate ester) available under the trade name REOFOS 35 from Lanxess Aktiengesellschaft, Cologne, Germany; flame retardant toluene diphenyl phosphate (available under the trade name KRONITEX CDP) or zinc borate (available under the trade name ZB-467) (both from Lanxess Aktiengesellschaft); and flame retardant enhancers available under the trade names FIREBLEND AF-100 (from The St. Louis Group of Indianapolis, IN, USA) and ADINS FIREPROOF 20 (from Tolsa SA, Madrid, Spain).

[0107] In some embodiments, one or more first flame retardant components may be included in the composition, and the total amount of the one or more first flame retardant components in the composition is at least 10%, 15%, 17%, 20%, 25%, 30%, 40%, 50%, 60%, or at least 70% by weight based on the total weight of the composition. In some embodiments, one or more first flame retardant components may be included in the composition, and the total amount of the one or more first flame retardant components in the composition is about 10%, 15%, 17%, 20%, 25%, 30% or 35%, to 40%, 45%, 50%, 55%, 60%, 64% or about 70% by weight based on the total weight of the composition, or a weight percentage between any pair of the above values.

[0108] In embodiments having two components, the first flame retardant component may be included in at least one of the first or second components. In some embodiments, the first flame retardant component may be included in both the first component and the second component.

[0109] In some embodiments, the first flame retardant component is included in at least one of the first or second components at a weight percentage of at least 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60%, or at least 70%, based on the total weight of the components (first or second components) in which the first flame retardant component is present. The first flame retardant component can be included in at least one of the first or second components at a weight percentage of greater than 0%, about 10%, about 15%, 17%, about 20%, about 25%, or about 30%, to about 40%, about 50%, or about 60%, about 70%, or any weight percentage between any pair of the above values, based on the total weight of the components (first or second components) in which the first flame retardant component is present.

[0110] In some embodiments, two or more first flame retardant components may be included in at least one of the first or second components, and the total amount of the one or more first flame retardant components in the first or second component is based on the total weight of the component (first or second component) in which the two or more first flame retardant components are present, at least 10%, 15%, 17%, 20%, 25%, 30%, 40%, 50%, 60% or at least 70% by weight. In some embodiments, two or more first flame retardant components may be included in at least one of the first or second components, and the total amount of the one or more first flame retardant components in the first or second component is based on the total weight of the component (first or second component) in which the two or more first flame retardant components are present, about 10%, 15%, 17%, 20%, 25%, 30% or 35%, to 40%, 45%, 50%, 55%, 60%, 64% or about 70% by weight, or a weight percentage between any pair of the above values.

[0111] The first flame retardant in the composition in an appropriate amount will provide a suitable flame retardant level without compromising other desirable properties. For example, in some cases, when there is an inappropriately high amount of flame retardant, the stiffness, hardness, flexibility, compressive strength, durability, modulus or structural elasticity of certain foam compounds may be inappropriate. For example, in some embodiments, the first flame retardant component in a foam (such as a polyurethane foam) for providing a suitable flame retardant level and providing a compound with suitable mechanical or structural properties can be based on the total weight of the polyurethane foam. 10%, 15%, 20%, 25%, about 30% or about 35%, to about 40%, about 45%, about 50%, about 55% or about 60% of the amount. In some embodiments, a suitable weight percentage of the first flame retardant component in a polyurethane foam (such as a polyurethane foam) for providing a suitable flame retardant level and providing a compound with suitable mechanical or structural properties can be an amount of at least 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55% or at least 60% based on the total weight of the foam. Second flame retardant component

[0112] The composition may include a second flame retardant component that is different from the first flame retardant component. In some embodiments, the composition includes two or more flame retardant components. In some embodiments, the composition is formed by two or more components, the first component may include a first flame retardant component, and the second component may include a second flame retardant component.

[0113] The second flame retardant component can be a liquid at room temperature. The second flame retardant component can be a solid at room temperature. In some embodiments, the first flame retardant component can be a liquid at room temperature, and the second flame retardant component can be a solid at room temperature. For example, the second flame retardant component can be in powder form at room temperature.

[0114] In some embodiments, the second flame retardant component may be a non-halogenated flame retardant. In some embodiments, the flame retardant component may be a halogenated flame retardant.

[0115] In some embodiments, the preferred second flame retardant component may be a graphite-based flame retardant. For example, a graphite-based flame retardant, such as expandable graphite, may be suitable as the second flame retardant component. For example, the first flame retardant component may be a liquid at room temperature, while the second flame retardant component may be a graphite-based flame retardant in powder form at room temperature.

[0116] In some embodiments, suitable commercially available flame retardant components that can be used as the second flame retardant component include graphite-based flame retardants sold under the trade name GRAFGUARD (from NeoGraf Solutions, LLC, Lakewood, OH, USA), graphite-based flame retardants sold under the trade name NYAGRAPH 35 (from Nycol Nanotechnologies, Ashland, MA, USA); phosphorus flame retardants (isopropylated triaryl phosphates) available from Lanxess Aktiengesellschaft, Cologne, Germany under the trade name REOFOS 35; flame retardants toluene diphenyl phosphate (available under the trade name KRONITEX CDP) or zinc borate (available under the trade name ZB-467) (both from Lanxess Aktiengesellschaft); red phosphorus flame retardants available under the trade name EXOLETRP 607 (from Clariant AG, Muttenz, Switzerland); and red phosphorus flame retardants available under the trade name EXOLETAP ammonium polyphosphate available under the trade name EXOLIT OP 945 or diethyl phosphinate available under the trade name EXOLIT OP 945 (both from Clariant); melamine polyphosphate available under the trade name MELAPURE 200 (from BASF, Ludwigshafen, Germany); CHARMORE PT40 (from Perastorp AB, and flame retardant enhancers available under the trade names FIREBLEND AF-100 (from The St. Louis Group of Indianapolis, IN, USA) and ADINS FIREPROOF 20 (from Tolsa SA, Madrid, Spain).

[0117] In embodiments having two components, the second flame retardant component may be included in at least one of the first or second components. In some embodiments, the second flame retardant component may be included in both the first component and the second component.

[0118] In some embodiments, a second flame retardant component can be included in the composition and the total amount of the second flame retardant component in the composition is at least 0.5%, at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or at least 20% by weight based on the total weight of the composition. In some embodiments, a second flame retardant component can be included in the composition, and the total amount of the second flame retardant component in the composition is greater than 0%, 0.5%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, or about 8%, to about 9%, about 10%, about 11%, about 12%, about 13%, about 14, about 15%, about 16%, about 17%, about 18%, about 19%, about 20% weight percent, or a weight percent between any pair of the above values, based on the total weight of the composition.

[0119] In some embodiments, the second flame retardant component may be present in at least one of the first or second components in an amount of at least 0.5%, at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, or at least 20% by weight based on the total weight of the component (the first or second component) in which the second flame retardant component is present. In some embodiments, the second flame retardant component is present in at least one of the first or second components at a weight percent of greater than 0%, 0.5%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, or about 8%, to about 9%, about 10%, about 11%, about 12%, about 13%, about 14, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or a weight percent between any pair of the foregoing values, based on the total weight of the component (the first or second component) in which the second flame retardant component is present.

[0120] In some embodiments, two or more second flame retardant components may be present in at least one of the first or second components, and the total amount of the two or more second flame retardant components in the first or second component is at least 0.5%, at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or at least 20% by weight based on the total weight of the component (first or second component) in which the two or more second flame retardant components are contained. In some embodiments, two or more second flame retardant components may be present in at least one of the first or second components, and the total amount of the two or more second flame retardants in the first or second component is greater than 0%, 0.5%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7% or about 8%, to about 9%, about 10%, about 11%, about 12%, about 13%, about 14, about 15%, about 16%, about 17%, about 18%, about 19%, about 20% by weight, or a weight percentage between any pair of the above values, based on the total weight of the component (the first or second component) in which the two or more second flame retardant components are contained.

[0121] In some embodiments, the first flame retardant component can be present in one or both of the first component and the second component in an amount greater than 0%, about 10%, about 15%, about 17%, about 20%, about 25% or about 30%, to about 40%, about 50%, or about 60%, about 70%, or a weight percentage between any pair of the above values, based on the total weight of the component (the first or second component) in which the first flame retardant component is present; and the second flame retardant component can be present in at least one of the first or second components in an amount greater than 0%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7% or about 8%, to about 9%, about 10%, about 11%, about 12%, about 13%, about 14%, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or a weight percentage between any pair of the above values, based on the total weight of the component (the first or second component) in which the second flame retardant component is present.

[0122] It has been found that suitable amounts of the first and second flame retardant components will provide suitable flame retardancy levels without compromising other desirable properties. For example, suitable weight percentages of the second flame retardant component in a foam compound (such as a polyurethane foam) for providing suitable flame retardancy levels and providing a compound with suitable mechanical or structural properties can be greater than 0%, about 1%, about 2%, about 3%, about 4%, about 5%, about 6%, about 7%, or about 8%, to about 9%, about 10%, about 11%, about 12%, about 13%, about 14, about 15%, about 16%, about 17%, about 18%, about 19%, about 20%, or weight percentages between any pair of the above values, based on the total weight of the foam compound. In some embodiments, suitable weight percentages of the second flame retardant component in a foam compound (such as a polyurethane foam) for providing a suitable flame retardant level and providing a compound with suitable mechanical or structural properties can be an amount of at least 0.5%, at least 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or at least 20% based on the total weight of the foam compound. Optional additional additives

[0123] The composition may optionally include additional additives, either as separate components or mixed into one or more of the components described above to form the first and / or second components.

[0124] Examples of additional additives that can be added to either or both of the first or second components include, but are not limited to, crosslinking agents, chain extenders, wetting agents, thixotropes, nucleating agents, surfactants, diluents, anti-settling agents, flame retardant reinforcing agents, and components and combinations thereof. In some embodiments, optional additional additives include waxes, release agents, antioxidants, reinforcing fillers, pigments, heat stabilizers, UV stabilizers, plasticizers, rheology modifiers, processing aids, lubricants, release agents, or components or combinations thereof. Suitable reinforcing fillers include mineral fillers and glass fibers.

[0125] Further examples of additional components include catalysts. In examples of polyurethane compositions, any conventional catalyst known to those skilled in the art can be used to react the isocyanate compound with the isocyanate-reactive compound and the remaining components. Suitable catalysts include, but are not limited to, triol catalysts, tetraol (tetra polyol) catalysts or tertiary amine catalysts. Further examples of suitable catalysts include various alkylamines, alkyl ethers or alkyl mercaptan ethers, such as those of bismuth or tin, wherein the alkyl moiety has 1 to about 20 carbon atoms. Some examples include bismuth octoate, bismuth laurate, etc. Other catalysts include various tin catalysts, such as stannous octoate, dibutyltin dioctoate, dibutyltin dilaurate, etc.

[0126] The optional additional additives disclosed herein may be present in the composition at a weight percentage of greater than 0%, about 0.1%, about 0.5% or about 1%, to about 5%, about 10%, about 20% or about 30%, or between any pair of the above values, based on the total weight of the composition. The weight percentage of the optional additional additive may apply to the total amount of all additional additives present or to each additional additive individually.

[0127] In the example of polyurethane composition, the amount of catalyst present can be greater than 0%, about 0.02%, about 0.05% or about 0.1%, to about 0.25%, about 0.75% or about 1%, or a weight percentage between any pair of the above values, based on the total weight of the composition. In some embodiments, the crosslinking agent or wetting agent can be greater than 0%, about 0.1%, about 0.5% or about 1%, to about 5%, about 7% or about 10% weight percentage, or a weight percentage between any pair of the above values, based on the total weight of the composition. In some embodiments, a surfactant, such as a surfactant suitable for stabilizing the foam structure or helping to wet out, can be greater than 0%, about 0.1%, about 0.5% or about 1%, to about 2%, about 3% or about 4% weight percentage, or a weight percentage between any pair of the above values, based on the total weight of the composition. In some embodiments, the nucleating agent may be present in the composition at a weight percent of greater than 0%, about 0.1% or about 0.5%, to about 1%, about 1.5% or about 2%, based on the total weight of the composition, or a weight percent between any pair of the foregoing values. Preparation of the composition

[0128] In embodiments of compositions having only a first component, the composition can be prepared by combining the first component with at least one flame retardant component. For example, a silicone-based flame retardant composition can be prepared by combining a first component including a silicone-based component with at least one of a first flame retardant component and a second flame retardant component.

[0129] In embodiments of compositions having more than one component, such as two-component compositions, the composition can be prepared by combining a first component with a second component, and at least one of a first flame retardant component and a second flame retardant component. In some embodiments, the composition can be prepared by combining a first component with a second component, and at least one of the first component and the second component can include at least one of a first flame retardant component and a second flame retardant component. Polyurethane Compounds

[0130] In embodiments of compositions having more than one component, such as two-component compositions, the first component and the second component are combined to form a composition having a flame retardant component. For example, in embodiments of polyurethanes forming flame retardant compounds, the first component and the second component are mixed to form a composition having at least one flame retardant component. After mixing the first component and the second component, the composition can be a blend of a polyurethane component and at least one flame retardant component. The flame retardant component system can include at least one or both of a first flame retardant component and a second flame retardant component. The components of the composition having one or more flame retardants are reacted to form a flame retardant polyurethane compound.

[0131] In some embodiments, for example, in the embodiment of the polyurethane forming the flame retardant compound, the polyol can be included in the composition in an amount of at least 5%, about 10%, about 20%, about 30% or about 40%, to about 50%, about 60%, about 70% or at least about 80% by weight based on the total weight of the composition. In the embodiment of the polyurethane forming the flame retardant compound, the polyether polyol can be included in the composition in an amount of at least 10%, about 20%, about 30% or about 40%, to about 50%, about 60%, about 70% or at least about 80% by weight based on the total weight of the composition. In the embodiment of the polyurethane forming the flame retardant compound, the polyether polyol can be included in the composition in an amount of about 5%, about 10%, about 20%, about 30% or about 40%, to about 50%, about 60%, about 70% or about 80% by weight or in an amount of any pair of weight percentages between the above values.

[0132] In some embodiments, the ratio of the weight of the isocyanate compound to the total equivalent weight of the isocyanate-reactive components can be from about 0.60, about 0.65, about 0.70, or about 0.75, to about 0.80, about 0.85, about 0.90, or about 0.95, or a ratio between any pair of the foregoing values. In some embodiments, the ratio of isocyanate compound to isocyanate-reactive compound is selected to use an excess of reactive isocyanate equivalents relative to the total number of isocyanate-reactive groups on the isocyanate-reactive compound.

[0133] Any known method for reacting the first component with the second component can be used. In the embodiment comprising the polyurethane composition, any method known to those skilled in the art for merging the first component and the second component to manufacture polyurethane foam can be used. In some embodiments, the merging method can be a "one-shot" method, in which all reactants are mixed and the appropriate time for the reaction is started. In some embodiments, the reactants can be mixed before the composition is placed and the appropriate time for the reaction is made. In some embodiments, the reactants can be mixed when the composition is placed so that the reaction starts when the composition is placed. For example, the composition can be mixed, and the reaction of the components is carried out for more than 1 second, and then the composition is dispensed into a container so that the composition is cured therein. The composition can be dispensed into a container so that the composition is mixed when it is cured therein, so that the reaction of the components starts immediately (less than 2 seconds) or starts simultaneously after the composition is dispensed into a container so that the composition is cured therein. Foam Compounds

[0134] After curing, the compound can be in the form of foam. For example, as the composition cures, the curing reaction can produce voids in the composition so that the resulting compound includes a cured composition that defines voids throughout the compound. The voids can be filled with a gas. The voids can be formed by curing of the composition, for example, the reaction of the first component with the second component can release a gas that forms bubbles in the composition. The voids can be formed by stirring the composition, for example, by blowing a gas such as air or nitrogen into it as the composition cures.

[0135] For example, the composition can be a liquid mixture formed by components that react with each other and release gas, and the gas forms a void in the form of bubbles defined by the composition. The liquid composition can solidify and form a compound in the form of a foam when solidified, which consists of a solidified composition that defines voids throughout the compound. Compared with the case where the potting compound is a solid block without voids, the density of the foam compound is lower. The foam can be closed-cell or open-cell. Closed-cell refers to a foam with a cavity that forms discrete air pockets that are completely surrounded by solid material. Open-cell refers to a foam with a cavity that forms air pockets that are interconnected.

[0136] In some embodiments, the composition may include microballoons. As the composition hardens, the microballoons may solidify in the hardened composition and become part of the resulting compound, thereby producing a foam form.

[0137] In some embodiments, the density of the compound in foam form is lower than the combined density of the components forming the composition when the components are all in liquid phase. In some embodiments, the compound has a density of not more than 0.6 g / cc, not more than 0.5 g / cc, not more than 0.4 g / cc, not more than 0.3 g / cc, not more than 0.2 g / cc, not more than 0.18 g / cc, not more than 0.16 g / cc, not more than 0.14 g / cc, not more than 1.2 g / cc, not more than 1.0 g / cc or even not more than 0.05 g / cc after solidification. For example, the compound can be in foam form and the foam can have a density of about 0.02 g / cc, about 0.05 g / cc, about 0.10 g / cc, about 0.20 g / cc, to about 0.30 g / cc, about 0.40 g / cc, about 0.50 g / cc or not more than 0.6 g / cc or a density between any pair of the above values. Flame Retardancy

[0138] The compositions disclosed herein are suitable for forming foam compounds that exhibit a suitable level of flame retardancy when measured with a sample of the compound having a dimension of no longer than 150 mm in length by 13 mm in width and a thickness of 1.0 millimeters (mm), 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, or 2.1 mm, to 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, or 7.0 mm, or a thickness between any pair of the foregoing values.

[0139] The compositions disclosed herein are suitable for forming compounds that exhibit at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the compound having a dimension of no greater than 150 mm long by 13 mm wide and a thickness of no greater than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even no greater than 1.0 mm; for example, a thickness of 1.0 millimeter (mm), 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, or 2.1 mm, to 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, or 7.0 mm, or a thickness between any pair of the foregoing values.

[0140] In some embodiments, the compositions disclosed herein are suitable for forming compounds that exhibit at least V1 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the compound having a size of no more than 150 mm long by 13 mm wide and a thickness of no more than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even no more than 1.0 mm; for example, a thickness of 1.0 millimeters (mm), 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, or 2.1 mm, to 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, or 7.0 mm, or a thickness between any pair of the foregoing values.

[0141] In some embodiments, the compositions disclosed herein are suitable for forming compounds that exhibit at least a V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the compound having a dimension of no greater than 150 mm long by 13 mm wide and a thickness of no greater than 9.5 mm, 6.35 mm, 3.2 mm, 1.6 mm, or even no greater than 1.0 mm; for example, a thickness of 1.0 millimeters (mm), 1.1 mm, 1.2 mm, 1.3 mm, 1.4 mm, 1.5 mm, 1.6 mm, 1.7 mm, 1.8 mm, 1.9 mm, 2.0 mm, or 2.1 mm, to 2.2 mm, 2.4 mm, 2.5 mm, 2.6 mm, 2.8 mm, 3.0 mm, 3.5 mm, 4.0 mm, 4.5 mm, 5.0 mm, 5.5 mm, 6.0 mm, 6.5 mm, or 7.0 mm, or a thickness between any pair of the foregoing values. Potting Compound

[0142] The composition disclosed herein is suitable for forming a potting compound. The composition can be used to pot one or more batteries. The composition can be used to pot a plurality of batteries in a battery module. The compound can be used to pot the battery and provide mechanical stability and flame retardancy after curing. The potting material can be in the form of a foam.

[0143] In some embodiments, the potting compound comprises a polyurethane foam. The potting compound may be formed from a polyurethane composition that is liquid before curing and hardens into a foam form as the potting compound. In some embodiments, the potting compound is formed from a polyurethane foam having a low density and comprising a flame retardant.

[0144] The composition disclosed herein is suitable for forming a potting compound having low density, flame retardant and foam. The potting compound is suitable for forming a battery module. The composition disclosed herein is suitable for forming a potting composition having suitable flowability to form a potting compound having a substantially uniform height throughout the battery module.

[0145] Figure 1 is a perspective view of an exemplary battery module 10. Figure 1 As shown in , the battery module 10 includes a battery 20 and a battery housing 22. In some embodiments, the battery 20 may be placed in the battery housing 22 and potted in a potting compound 24. The battery 20 can be any suitable shape, which generally has a bottom 30, a top 32, and a length defined therebetween. The battery housing 22 can be any suitable shape for accommodating the battery 20, and generally has a bottom 36, a top 38, and a wall 40 defined therebetween. The bottom 36 of the battery housing 22 defines an inner surface and an outer surface; the wall 40 of the battery housing defines an inner surface and an outer surface. The battery housing 22 defines an enclosed space having an interior volume. The potting compound 24 is placed in the battery housing 22 and occupies a portion of the interior volume of the battery housing 22. The potting compound 24 generally has a top 42, a bottom 44, and a height defined therebetween.

[0146] Figure 2 yes Figure 1 A top view of the battery module 10 is shown in FIG. Figure 2As shown in , the battery housing 22 forms an enclosed space large enough to surround the battery 20 and other components, such as wires or connectors. The enclosed space defines the internal volume of the battery housing 22. The bottom 36 of the battery housing 22 can be closed and accommodate any contents of the enclosed space. The top 38 of the battery housing 22 can define an opening. The top 38 and / or the opening can have a shape and size suitable for receiving a cover, which can be closed to separate the internal volume of the enclosed space from the outside of the battery housing 22. The cover can be configured to seal the internal volume of the enclosed space from the outside of the battery housing 22 to prevent potential hazards, such as fluid or flame intrusion. The battery housing 22 can be designed and configured to provide mechanical or structural support for the battery 20. The battery housing 22 can also be configured to provide protection to prevent moisture, heat, cold or any other potential factors that may cause damage to the battery 20.

[0147] As shown, in one possible arrangement, the battery 20 can be formed as a cylinder. In further examples, the battery 20 can be formed into any suitable shape or size as desired, such as a cube, a sphere, a cuboid, a tetrahedron, a cone, a rhombus, a hemisphere, a pouch or a pyramid, etc. Figure 1 The battery shown in FIG. 1 is shaped as a cylinder having a bottom 30, a top 32, and a wall extending between the bottom 30 and the top 32. The bottom 30 can be the positive terminal of the battery 20, or can be the negative terminal of the battery 20, depending on the desired orientation. As shown, the bottom 30 of the battery 20 is placed in the potting compound 24. The potting compound 24 occupies a portion of the interior volume of the battery housing 22 and extends substantially equal distances from the bottom 36 to the top 38 of the battery housing 22 at various points along the wall 40.

[0148] Electric cells can be used to form a battery. For example, multiple electric cells can be combined to form a single battery with a higher voltage or amperage than a single cell.

[0149] Figure 36 is a front view of a battery module 50 including cells 52. Each cell 52 has a bottom 60, a top 62, and a wall defining a certain length therebetween. The cells 52 can be placed in a battery housing 64. The cells 52 define a gap 80 between each cell and an adjacent cell. The gap 80 has a certain width. The battery housing 54 has a bottom 66, a top 68, and a wall 70 therebetween. The bottom 66 and the wall 70 define an enclosed space. The enclosed space of the battery housing 54 defines an internal volume. The internal volume of the battery housing 54 has a volume suitable for receiving the cells 52 and the potting compound 56. The potting compound 56 has a bottom 82, a top 84, and a height 86 therebetween. The bottom 82 of the potting compound 56 is adjacent to the inner surface of the bottom 66 of the battery housing 54. As shown, the top 84 of the potting compound 56 is between the bottom 66 and the top 68 of the battery housing 54. Typically, the top 84 of the potting compound 56 is lower than the top 62 of the battery 52 , although it is contemplated that in alternative arrangements the top 62 of the battery 52 may be lower than the top 84 of the potting compound 56 .

[0150] As shown, multiple cells 52 can be arranged adjacent to each other, with the orientation of each cell 52 such that similarly charged terminals face the same direction. Wires can be connected to the ends of the cells 52. The wires can be combined in electrical communication to combine the current from the cells 52 to form a battery with a combined current or voltage, for example. The battery module 50 can be used to power any of a number of applications, such as household appliances, outdoor electrical equipment, or vehicles, such as cars or boats.

[0151] To combine the cells 52 to form a battery module, the cells 52 are connected with wires that conduct current from the cells 52. The cells 52 are typically arranged adjacent to each other, such as in rows or stacks, to form an orderly arrangement that is easy to use and / or connect the wires to the battery terminals. In order to save space and to form a small battery, the cells 52 can be placed in close proximity to each other. For example, the cells 52 can be arranged in rows or in a grid with the positive and negative terminals facing the same direction. The cells 52 can be placed in an orderly arrangement and contained in a battery housing 54, although it is contemplated that in some cases, a battery module can be formed without a battery housing 54. For example, the cells 52 can be bundled together using alternative fastening devices, such as wires, ropes, straps, etc., to, for example, secure the cells 52 in a bundle.

[0152] In some cases, it may be desirable to provide a portable battery module, such as in the case of starting the ignition of a vehicle or driving a vehicle with a battery, as some examples, the vehicle is such as a motorcycle, a car or a boat. In the case of wishing that the battery is portable, it is generally preferred to provide a battery with a stable structure and capable of withstanding forces, such as shocks and / or vibrations. In some cases, it is also desirable to provide a battery capable of withstanding extreme temperatures, including temperatures outside the normal operating temperature of the battery. For example, in some cases, the battery may be subjected to high heat, and possibly open flames. A possible source of fire may be one or more batteries, such as due to an electrical short circuit or if the structure of the battery wall is damaged. An exemplary device that can be used to protect the battery 52 is a potting compound 56. The potting compound 56 may be associated with the battery 52, such as being arranged around the battery 52 along one or more of the top, bottom or wall of the battery. The battery 52 may be embedded or embedded in the potting compound 56, which keeps the battery 52 in a spatial relationship relative to each other and / or relative to the spatial relationship of the battery housing 54.

[0153] like Figure 3 , the cells 52 are disposed in a potting compound 56. The potting compound 56 is disposed around each cell 52. In the case where the battery contains a plurality of cells 52, the potting compound 56 may be disposed around each cell and in the gaps 80 or spaces defined between the individual cells 52. In the case where the battery is contained within a battery housing 54, the potting compound 56 may be disposed between the cell 52 and the battery housing 54. The potting compound 56 may be disposed to provide suitable structural or mechanical support to the cells 52.

[0154] In some cases, the cells 52 may be arranged with a suitable distance between adjacent cells 52 so that in the event of a leak or fire, the individual cells 52 are thermally and / or fluidically isolated from each other. In some cases, the cells 52 may be arranged with a suitable distance between adjacent cells 52 so that a suitable thickness of potting compound 56 is arranged between adjacent cells 52 to provide sufficient shock absorption to prevent damage to the cells 52. The size of the space or gap 80 between adjacent cells 52 and / or the battery housing 54 may be selected based on many variables, including but not limited to the size and / or weight of the individual cells, the operating temperature of the individual cells, the size of the individual cells, and the intended use of the battery module 50. In some examples, the size of the space between adjacent cells may be greater than 0 mm, about 0.25 mm, about 0.50 mm, about 0.75 mm, to about 1.0 mm, about 1.5 mm, about 2.0 mm, about 2.5 mm, or about 3.0 mm, or a size between any pair of the above values, although battery modules with other configurations are further contemplated. In some examples, the space between the cells and the battery housing may have a size of greater than 0 mm, about 1.0 mm, about 2.0 mm, about 3.0 mm, to about 10 mm, about 12 mm, or about 14 mm, although battery modules having other configurations are further contemplated.

[0155] In some embodiments, the potting compound 56 can be formed by first molding a material such as a potting composition into a suitable shape, which has a space defined by the potting compound 56 for accommodating one or more batteries 52. The potting compound 56 can be formed by molding the potting composition into a certain size and shape to place the potting compound 56 in the battery housing 54 and define one or more spaces to fix the one or more batteries 52 placed in these spaces.

[0156] In some embodiments, the potting compound 56 can be formed by first arranging the batteries 52 into the desired final position (e.g., fixed together with wires or in the battery housing 54). The batteries 52 can be fixed in place in a spatial relationship relative to each other using a mold or a bracket. The batteries 52 can be fixed in place and placed in a mold or other housing that surrounds the batteries 52. In a further example, the batteries 52 can be arranged in a desired final position in a spatial relationship relative to each other and placed in the battery housing 54, such as resting on the inner surface of the bottom 66 of the battery housing 54. Once the desired arrangement of the batteries 52 is completed, the potting compound 56 can be formed by flowing the potting composition around the batteries 52 and through the gaps 80 or spaces defined between adjacent batteries 52. The potting composition can be applied as a liquid so that the potting composition flows through the gaps 80 defined between adjacent batteries 52 and between the batteries 52 and the wall 70 of the battery housing 54. As described above, the potting composition can be configured to be applied as a liquid, which hardens into a solid after application and forms the potting compound 56. In some embodiments, the potting composition may be reactive such that the potting composition is applied as a liquid that flows around the cells 52 and through the gaps 80 defined between adjacent cells 52 and then hardens after the reaction is complete.

[0157] The potting composition can flow through the gaps 80 between adjacent cells 52 and settle at a level height in the gaps 80 or spaces around the cells 52 and defined between the cells 52. Figure 3 , the potting composition can be poured into the battery housing 54 having the cells 52 disposed therein. The liquid potting composition has sufficient flowability prior to curing to allow the liquid potting composition to flow through the space defined by the gaps 80 between adjacent cells 52 and / or between the cells and the battery housing 54. The liquid potting composition has sufficient flowability to stabilize at a substantially level height prior to curing to form the potting compound.

[0158] As used herein, flowability refers to the ease of movement of a substance under a specific set of conditions. Some of these conditions may include the temperature of the substance, the viscosity of the substance, or the size of the space through which the substance can flow. For example, for a liquid potting composition, the flowability of the liquid determines how it behaves when poured and how well it flows between adjacent cells and / or between a cell and a battery housing. In some embodiments, the potting composition is self-leveling.

[0159] In a preferred embodiment, the potting composition has sufficient flowability to allow the potting composition to be poured around one or more cells 52 and to stabilize at a substantially level height around the one or more cells 52 before the potting composition hardens to form the potting compound 56. For example, the potting composition has sufficient flowability to allow the potting composition to flow around an object such as a cell 52 in the container after the potting composition is poured into a container such as a battery housing 54, and the potting composition can be spread and leveled to a height 86 before curing to form the potting compound, and when the height 86 is measured at any two or more locations around the cell 52 in the container (e.g., at various locations of the battery housing 54), the height is substantially the same. The potting composition has sufficient flowability to be spread so that the potting composition can flow around an object before curing to form the potting compound, and after the potting composition has cured, when the height is measured at various locations around the cell 52 (e.g., at various locations of the battery housing 54), the potting composition has substantially the same height 86.

[0160] Providing the potting composition with sufficient flowability to form a substantially level height can help to form a potting compound that encapsulates each battery at substantially the same height. This provides a consistent amount of encapsulation around each battery. This can ensure proper encapsulation of the battery 52 to ensure a suitable level of protection, such as a suitable amount of structural stability and / or a suitable amount of flame retardant to contain a fire or flame. Providing the potting compound with a substantially level height can help to balance the weight of the battery module 50 throughout the battery module 50. Proper balance or weight distribution helps the battery module 50 remain stable, for example when used in a moving vehicle. A properly balanced battery module may be preferably used in a vehicle because it may have a lower tendency to shake or tilt in response to external forces (such as left-right or front-to-back acceleration).

[0161] Providing a low-weight battery module may be preferred because this can make the battery module more portable and can reduce the energy required to move the battery module. For example, in an electric vehicle, it may be advantageous to provide a lighter battery module that can generate the same amount of power as a heavier embodiment. One option for achieving this is to use the same type and number of batteries, but reduce the weight of other components. Reducing the density of the potting compound will help reduce the overall weight of the potting compound without reducing other desirable qualities. Providing a flame retardant component also helps reduce the possibility of uncontrolled fire in the battery module.

[0162] After being fully cured, the potting compound may have elasticity and help to cushion the impact or vibration applied to the battery module during use of the battery module. This may help prevent safety issues caused by collisions between batteries and / or separation of batteries from wires.

[0163] The cured potting compound may have a certain degree of porosity, which is controlled so that if one battery involves safety issues and leaks, any leaked material such as fluid or gas will be retained and isolated by the potting compound disposed between adjacent batteries, thereby helping to improve the safety performance of the battery module. In addition, the battery module has the advantages of simple structure, low density, small size and low cost.

[0164] Figure 4 is a perspective view of an exemplary battery module 100. Figure 4 As shown in , the battery module 100 includes a battery 120 and a battery housing 122. In some embodiments, the battery module 100 includes more than one battery 120. The battery 120 can be any suitable shape, generally having a bottom 130, a top 132, and a length defined therebetween. The battery housing 122 can be any suitable shape for accommodating the battery 120 within the battery housing 122. The battery housing 122 can be any suitable three-dimensional shape, generally having a bottom 136, a top 138, and a wall 140 defined therebetween. The bottom 136 of the battery housing 122 defines an inner surface and an outer surface; the wall 140 of the battery housing 122 defines an inner surface and an outer surface. The battery housing 122 defines an enclosed space having an interior volume.

[0165] As shown, the battery 120 can be disposed within a battery housing 122. Also as shown, the battery 120 is associated with a potting compound 124. The potting compound 124 is disposed within the battery housing 122 and occupies a portion of the interior volume of the battery housing 122.

[0166] In some embodiments, the battery housing 122 forms an enclosed space surrounding the battery 120 and other components, such as wires, terminals, or connectors. The enclosed space defines the internal volume of the battery housing 122. The top 138 of the battery housing 122 may define an opening. The top 138 may have a shape and size suitable for receiving a cover, which can be closed to separate the internal volume of the enclosed space from the outside of the battery housing 122. The battery housing 122 can be configured to provide mechanical or structural support for the battery 120. The battery housing 122 can be configured to provide protection from potential damage to the battery 120, such as moisture, heat, cold, chemicals, shock, vibration, puncture, or flame. In some embodiments, the battery housing 122 can be configured to receive a potting compound 124 relative to the battery 120, including, for example, below the battery 120, between the first and adjacent batteries 120, above the battery 120, or between the battery 120 and the wall 140 of the battery housing.

[0167] In some embodiments, a method of positioning a potting compound 124 relative to a cell 120 includes first positioning the cell 120 within a battery housing 122. One or more cells 120 may be positioned together in the battery housing, defining a gap 180 between adjacent cells 120. In some embodiments, a gap 180 may also be defined between the cell 120 and the wall 140 of the battery housing 122. In some examples, the potting compound 124 may be prepared in a separate container and then poured into the battery housing 122. The components of the potting compound 124 may be mixed to form a composition that can be cured to form a foam, which may then be poured into the battery housing 122 and allowed to flow throughout the battery housing 122 between the cells 120. For example, the components of the potting compound 124 may be mixed to form a composition that can be cured to form a foam, which may then be applied to the top 132 of the cell 120. The potting compound 124 may be added to place a layer of the potting compound 124 having a certain thickness on the top 132 of the cell 120. In some embodiments, the potting compound 124 can be disposed in the gaps 180 between adjacent cells 120. The potting compound 124 can be disposed in the gaps 180 between the wall 120 and the cells 120. The potting compound 124 can be disposed to define a space between the top of the potting compound 124 and the top 138 of the battery housing 122. In some embodiments, a quantity of the potting compound 124 can be cured into a suitable preformed shape, and the preformed shape can be added to the battery housing 122 in a suitable position relative to the cells 120.

[0168] Figure 5 2 is a top view of an exemplary battery module 200. The battery module 200 includes cells 220 arranged adjacent to each other. Figure 5 As shown in , the battery 220 is placed in a battery housing 222 having a top 238. The battery housing 222 defines an internal volume. As shown, the dimensions of the battery housing 222 are such that the battery 222 can be placed in the internal volume of the battery housing 222 and leave a space between the top 232 of the battery housing 222 and the top 232 of the battery 220. Also shown is a potting compound 224 placed in the internal volume of the battery housing 222. As shown, the potting compound 224 has a generally planar shape and extends along the top 232 of the battery 220. The potting compound 224 can be configured so that the user can access the terminal 290 of the battery 220. In some embodiments, the battery 220 includes a terminal 290 placed on the top 232 of the battery 220. The potting compound 224 can be placed around the terminal 290 and between the top 232 of the battery 220 and the top 238 of the battery housing 222.

[0169] In some embodiments, a method of positioning a potting compound 224 relative to a battery 220 includes first positioning the battery 220 within a battery housing 222. The potting compound 224 may be prepared in a separate container and then poured into the battery housing 222. A suitable amount of potting compound 224 may be added to position a layer of potting compound 224 having a certain thickness on the top 232 of the battery 220 and / or between adjacent batteries 22. In some embodiments, the potting compound 224 may be added so that the layer of potting compound 224 has a thickness suitable for covering the top 232 of the battery 220 and the terminal 290 protrudes through the thickness of the potting compound 224. The potting compound may maintain the battery 220 in a spatial relationship relative to each other, such as by potting or encapsulating the terminal 290 to fix the battery 220 relative to each other.

[0170] Figure 6 3 is an exploded view of an exemplary battery module 300. The battery module 300 includes cells 320 positioned adjacent to each other. In some embodiments, the battery module 300 includes a battery housing 322. The cells 220 are shown with terminals 290 positioned on the top 232 of the cells 220. A potting compound 324 associated with the cells 320 is also shown. Figure 6 As shown in , the battery 320 can have a generally planar shape. As shown, a section of the potting compound 224 has a generally planar shape. In some configurations, a section of the potting compound 324 can be disposed between adjacent batteries 320. For example, a section of the potting compound 324 can have a planar shape and be disposed parallel to the plane of the battery 320.

[0171] In some embodiments, the method of placing the potting compound 324 relative to the battery 320 includes first placing the battery 320 in a spatial relationship relative to each other, and then the potting compound 324 can be placed in the space defined between the adjacent batteries 320. For example, the potting compound 324 can be poured into the space between the adjacent batteries 320 and cured therein. As another example, the potting compound 324 can be cured and formed into a preformed section, which can then be placed in the space between the adjacent batteries 320. A suitable amount of potting compound 324 can be provided to arrange a piece of potting compound 324 with a suitable thickness between the adjacent batteries 220. In some embodiments, a piece of potting compound 224 can be provided so that the piece of potting compound 324 has a thickness suitable for providing a suitable flame retardant level. In some embodiments, the potting compound 320 can keep the batteries 320 in a spatial relationship relative to each other, such as absorbing the impact or vibration of the battery module 300. Example

[0172] The following non-limiting examples are included to further illustrate various embodiments of the present disclosure and do not limit the scope of the present disclosure. Test method: Viscosity test

[0173] The viscosity was measured with a Brookfield Viscometer Model RVF (from AMETEK Brookfield of Middleboro, MA) at a spindle speed of 50 rpm and an ambient temperature of 25° C. (77°±2° F.). The spindle used was No. 1 (up to 200 cps), No. 2 (up to 800 cps), No. 3 (up to 2,000 cps), or No. 4 (up to 4,000 cps), depending on the composition tested. Foam density test

[0174] Record the weight of the empty measuring device to within 0.1 gram.Measure the maximum capacity of the measuring device by filling it with water and recording in milliliters the amount of water required to fill the internal volume of the measuring device.

[0175] Weigh the components of the composition to be measured and add to the measuring device. Mix the components vigorously for 15 to 20 seconds. Scrape the sides and bottom of the measuring device thoroughly to ensure that all components are incorporated. Tap the measuring device violently on a hard surface to level the composition. Place the measuring device on a level surface, allow the composition to react and allow the resulting foam to rise freely without interference. Allow the foam to solidify for 60 to 70 minutes. After solidification, use a flat cutting tool, such as a knife or saw to cut the top of the foam bun that extends above the top of the measuring device to be flush with the top of the measuring device.

[0176] The measuring device containing the remaining cured composition is weighed and the weight in grams is recorded. The weight of the empty measuring device is subtracted from the weight of the measuring device containing the cured composition to obtain the weight of the cured composition. The density is calculated by dividing the weight of the cured composition by the volume of the measuring device.

[0177] Free Rise Density is the density of the portion of the cured composition remaining in the measuring device containing the cured composition after cutting away the top of the foam mass that extends above the top of the measuring device. Start of Rise Time Test

[0178] The Rise Start Time test is conducted by placing all of the components that form the composition to be measured in the container used to mix the composition. Once all of the components of the composition to be measured are placed in the mixing container, a timer is started and the components are mixed together.

[0179] Once the components of the composition to be measured are mixed together, the composition is placed in a measuring container and the height of the top surface of the composition in the measuring container is marked on the side of the container. The time when the top surface of the composition begins to rise from the marked starting height under the foaming effect of the chemical reaction of the components is the end point of the test. Top of Cup Time Test

[0180] The cup top time test is performed by placing all of the components that form the composition to be measured in a container for mixing the composition. Once all of the components of the composition to be measured are placed in the mixing container, a timer is started and the components are mixed together.

[0181] Once the components of the composition to be measured are mixed together, the composition is placed in a measuring container and a measuring rod (e.g., a tongue depressor) is placed across the top surface of the measuring container. The time when the composition to be measured rises under the foaming effect of the chemical reaction of the components and touches the measuring rod is the endpoint of the test. Burn Test

[0182] The combustion test was conducted according to UL 94 Plastics Flammability Test, Vertical Burning Test method. The combustion test sample strips were prepared by pouring the composition to be tested into a mold with the following dimensions: 150 mm long x 13 mm wide and with the thickness to be tested (1.0 mm, 1.6 mm, 3.2 mm, 6.35 mm or 9.5 mm). The sample to be tested was cured in the mold for 8 to 20 hours before removal. After molding, the sample strips to be tested were conditioned at an ambient temperature of 25 ± 2 ° C and 50 ± 5% RH for a minimum of 48 hours before testing.

[0183] A layer of cotton is placed under a Bunsen burner to catch possible drippings from the sample to be tested. The flame length of the Bunsen burner is set to about 2.5 cm (about 1 inch). The sample strip to be tested is suspended vertically above the Bunsen burner for 10 seconds for the first time. The flame is then removed and the sample strip is allowed to self-extinguish. The flame is then applied to the sample a second time, also for 10 seconds, and removed again to allow the sample strip to self-extinguish a second time. The amount of time until the sample is removed from the flame is measured.

[0184] The sum of the first and second amounts of time required for the sample to self-extinguish is used to determine the sample's V rating. Any ignition of a cotton layer located beneath the sample combined with the self-extinguishing time is used to determine the V rating.

[0185] The material is rated V0 if a single sample strip self-extinguishes within a maximum of 10 seconds after the sample strip is removed from the flame of the burner, the total self-extinguishing time for a group of 5 specimens is less than 50 seconds, and the cotton layer located under the Bunsen burner does not ignite.

[0186] The material is rated V1 if a single sample strip self-extinguishes within a maximum of 30 seconds after the sample strip is removed from the burner flame, the total self-extinguishing time for a group of 5 specimens is less than 250 seconds, and the cotton layer placed under the Bunsen burner does not ignite.

[0187] If a single sample strip self-extinguishes within a maximum of 30 seconds after the sample strip is removed from the burner flame and the total self-extinguishing time for a group of 5 specimens is less than 250 seconds but the cotton indicator is ignited by particles from the sample strip, the material is rated V2. Foam Core Integrity Test

[0188] Conduct the foam core integrity test on samples that have been subjected to the burn test. Allow each sample that has been subjected to the burn test to cool and then touch gently to remove any surface char and any incomplete sample sections. The sample strip should be touched gently to prevent damage to the strip. Measure and record the length of the portion of each sample that has been burned with a ruler on a flat surface. Foam Integrity Test

[0189] Sample strips for foam integrity testing were made using the sample preparation procedures described in the fire test.

[0190] The foam integrity test may be performed on the sample after it has been subjected to the combustion test. After the combustion test is completed, the sample that has been subjected to the combustion test is conditioned at a temperature of 25±2° C. and 50±5% RH for 24 hours.

[0191] Visually inspect the samples that have been subjected to the combustion test to determine the portion of the sample strip that has burned and the portion that has not burned during the combustion test. The sample strips are measured using an Instron 5967 (from Instron, Corp. of Norwood, MA) using a 1.5-inch diameter head. The Instron head is pressed into the portion of the sample strip that has not burned at a speed of 0.127 cm / min (0.05 inches / minute) and stopped when the Instron head has traveled approximately 50% of the total thickness of the sample strip. The Instron head is then pressed into the portion of the strip that has burned at a speed of 0.127 cm / min (0.05 inches / minute) and stopped when the Instron head has traveled approximately 50% of the total thickness of the sample strip.

[0192] The burned portion of the strip and the unburned portion of the strip are measured. The Instron provides a measure of the modulus of the sample strip. Self-Leveling Test

[0193] The self-leveling test can be used to determine compositions that form a substantially level height.

[0194] The composition to be tested is prepared as described in the foam density test. After mixing, the composition to be tested is poured into a container (such as a battery housing 54) containing an object (such as a battery 52), allowing the composition to be tested to flow between them. The size of each gap 80 between adjacent batteries 52 is about 1 mm to about 3 mm wide.

[0195] To determine the substantially level height, the height 86 of the potting compound 56 is measured from the bottom 82 of the potting compound 56 to the top 84 of the potting compound 56. The height 86 is measured at two or more locations of the potting compound 56. For example, a measurement may be taken near a wall of the battery housing 54, and another measurement may be taken near the center of the battery housing 54 (e.g., equidistant from two opposing sides of the housing). If the measured values ​​of the height of the potting compound taken at any two or more locations are within 20% of each other, then the potting compound has a substantially level height.

[0196] Additionally or alternatively, if the cells 52 have the same length and are the same distance from the bottom and / or top of the battery housing 54, then if each measurement of the distance of the potting compound 56 along the length of each cell 52 is within 20% of each other, the potting compound 56 is at a substantially level height. preparation

[0197] An exemplary method for forming sample compositions and compounds to be tested is described. This same method was used for all sample compositions, and the amounts of each component are listed in Tables 1 and 2 below. First and second component forming method

[0198] To form the first component, first add the liquid polyol to the mixing vessel. The mixer speed is between 25 and 30 rpm while adding the liquid polyol. Once all the liquid polyol is added, increase the mixer speed to between 600 and 800 rpm.

[0199] In the sample compositions including them, liquid glycerin, triethanolamine, polyether and anti-settling agent are then added to the mixing container. In the samples including them, thixotrop (fumed silica), nucleating agent and liquid first flame retardant component are then added to the mixing container. The contents of the mixing container are mixed for about 15 to about 20 minutes.

[0200] Distilled water was then added to the mixing vessel. In the samples that included them, the catalyst and surfactant were added while mixing the contents of the mixing vessel. In the samples that included them, the second flame retardant was then added. The contents of the mixing vessel were mixed for about 30 minutes to form the first component. After about 30 minutes, mixing was stopped and the first component was drained from the mixing vessel.

[0201] To form the second component, a liquid isocyanate is added to a mixing container. The liquid isocyanate is mixed at a mixer speed of 25 to 30 rpm while being added to the mixing container. In samples where the first or second flame retardant is included in the second component, the first and / or second flame retardant is then added to the mixing container. The contents of the mixing container are mixed for 15 to 20 minutes to form the second component. After 15 to 20 minutes, mixing is stopped and the second component is drained from the mixing container. Potting Compositions and Potting Compound Formation Methods

[0202] Pour appropriate amounts of the first component and the second component into a mixing container.

[0203] Place the higher density component first in the mixing vessel, then gently add the second component over the first. This process can help limit pre-reaction of the materials at the interface. Scrape the sides and bottom of each measuring vessel to ensure that as much of the material being measured as possible is added to the mixing vessel.

[0204] Start the timer and mix the contents of the mixing container vigorously with a flat-sided stirring utensil for 20 to 30 seconds until the mixture is uniform and consistent in appearance. Scrape the sides and bottom of the mixing container during mixing. After mixing, pour the contents of the mixing container immediately into the mold. Sample composition

[0205] The sample compositions were made by separately forming a first component (Part A) and a second component (Part B). The composition of Part A of each sample composition is shown in Table 1, and the composition of Part B of each sample composition is shown in Table 2. The components used to form the sample compositions are included herein, including trade names and suppliers where applicable.

[0206] Foaming agent (distilled water).

[0207] Liquid phenolic antioxidant (BNX 1035, from Mayzo, Inc., Suwanee, GA, USA).

[0208] Glycerin 99.5% (triol crosslinker / humectant) (from Dow Chemical Company, Midland, MI, USA).

[0209] Cationic polymer dispersant (ZEPHRYM PD-7000, from Croda International, Snaith, England).

[0210] Thixotrop (fumed silica) (AEROSIL 200 from Evonik Industries, Essen, Germany).

[0211] Zinc stearate (nucleating agent) (NB-60, from PMC Group, Memphis, TN, USA).

[0212] Brominated flame retardant (ethylene bistetrabromophthalimide) (SAYTEX BT-93, from Albemarle Corporation, Baton Rouge, LA, USA).

[0213] Low viscosity polyol (700M n PPG triol polyol) (ARCOL LHT-240 (available from Covestro AG, Leverkusen, Germany).

[0214] 5800M n SAN grafted polyether triol polyol (VORALUX HL 431, from The Dow Chemical Company).

[0215] Silicone surfactant (cellular surfactant) (VORASURF DC 5160, from The Dow Chemical Company).

[0216] The first FR enhancer (FIREBLEND AF-100, from The St. Louis Group of Indianapolis, IN, USA).

[0217] Second FR synergist (ADINS FIREPROOF 20, from Tolsa SA, Madrid, Spain).

[0218] 280M n PPG Tetra Polyol (amine polyol) (PLURACOL PEP 450, from BASF of Ludwigshafen, Germany).

[0219] First tertiary amine catalyst 1,4-diazabicyclo[2.2.2]octane solution (DABCO 33LV, from Evonik Industries, Essen, Germany).

[0220] Second tertiary amine catalyst (JEFFCAT DMDEE, from Huntsman Corporation, The Woodlands, TX).

[0221] Amine catalyst (DABCO DC 5LE from Evonik Industries).

[0222] Polymeric MDI-2.7 functionality (RUBINATE M, from Huntsman Corporation).

[0223] Modified liquid MDI (isocyanate-29% NCO) (ISONATE 143L, from The Dow Chemical Company).

[0224] Halogenated phosphate flame retardant (FYROL PCF, from ICL Industrial Products, St. Louis, MO, USA).

[0225] Expandable graphite (non-halogenated flame retardant) (GRAFGUARD, from NeoGraf Solutions, LLC, Lakewood, OH, USA).

[0226] Non-halogenated phosphate flame retardant (FYROLFLEX RDP from ICL Industrial Products).

[0227] Flame retardant plasticizer (butylated triphenyl phosphate) (PHOSFLEX 71B, from ICL Industrial Products).

[0228] Non-halogenated phosphorus-based flame retardant (FYROL A710 from ICL Industrial Products).

[0229] Brominated flame retardant (ethylene bistetrabromophthalimide) (SAYTEX BT-93, from Albemarle Corporation, Baton Rouge, LA, USA).

[0230] Phosphorus flame retardant (isopropylated triaryl phosphate) (REOFOS 35 from Lanxess Aktiengesellschaft, Cologne, Germany).

[0231] Flame retardant (cresyl diphenyl phosphate) (KRONITEX CDP from Lanxess Aktiengesellschaft).

[0232] Flame retardant (zinc borate based flame retardant / smoke suppressant) (ZB-467 from Lanxess Aktiengesellschaft).

[0233] Flame retardant performance enhancer (antimony trioxide) (AMSPEC SELECT, from Amspec Chemical Corporation, Gloucester City, NJ).

[0234] Red phosphorus flame retardant, available under the trade name EXOLET RP 607 (from Clariant AG, Muttenz, Switzerland).

[0235] Ammonium polyphosphate available under the trade name EXOLET AP 423 or aluminum diethylphosphinate available under the trade name EXOLIT OP 945 (both from Clariant).

[0236] Melamine polyphosphate available under the trade name MELAPURE 200 (from BASF, Ludwigshafen, Germany).

[0237] Pentaerythritol available under the trade name CHARMORE PT40 (from Perastorp AB, Sweden).

[0238] Flame retardant enhancers available under the trade names FIREBLEND AF-100 (from The St. Louis Group of Indianapolis, IN, USA) and ADINS FIREPROOF 20 (from Tolsa SA, Madrid, Spain).

[0239] For each sample, the final composition of each sample composition was formed by mixing Part A and Part B of each sample in a weight ratio of 100 to 86. The sample compositions were tested according to the above test method. The results and observations are listed in Table 3.

[0240] The sample compositions were formed into compound strips; each strip was 150 mm long x 13 mm wide and had a thickness of 1.0 mm, 1.6 mm, 3.2 mm, or 6.35 mm. The strips of the sample compositions were tested according to the above-described combustion test. The results of the combustion test for each sample composition at each thickness are listed in Table 4.

[0241] The burning samples were made by forming compound strips using compositions having different amounts of graphite-based flame retardants. The burning samples were tested according to the Foam Core Integrity Test described above. The results and observations are listed in Table 5.

[0242] The combustion samples were tested according to the Foam Integrity Test described above. The results and observations are shown in Table 6.

[0243] The changes in modulus, compressive strength, and load for each sample in Table 6 are shown in Table 7, which shows the differences in each burn sample before and after the foam integrity test was performed. Various modifications and additions may be made to the exemplary embodiments discussed without departing from the scope of the invention. For example, although the above embodiments refer to particular features, the scope of the invention also includes embodiments having different combinations of features and embodiments that do not include all of the above features.

Claims

1. A composition comprising: a first component comprising an isocyanate-reactive compound and a blowing agent; and a second component comprising an isocyanate compound; at least one of the first component and the second component comprises at least 15 wt % of a first flame retardant component that is liquid at a temperature of 25° C. to 35° C., based on the total weight of the composition; and At least one of the first component and the second component comprises at least 1 wt % of a second flame retardant component comprising expandable graphite, based on the total weight of the composition, The first component, the second component, the first flame retardant and the second flame retardant are configured to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RV viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of about 25°C.

2. The composition of claim 1, wherein the composition is configured to cure to form a foam compound that exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the foam compound having a thickness of no greater than 1 mm.

3. The composition of claim 1, wherein the second flame retardant is non-halogenated expandable graphite.

4. A composition comprising: a first component comprising an isocyanate-reactive compound and a blowing agent; a second component comprising an isocyanate compound; and At least one of the first component and the second component comprises at least 15 weight percent of the first flame retardant component based on the total weight of the composition, The composition is configured to cure to form a foam compound that exhibits at least a V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when measured with a sample of the foam compound having a thickness of no greater than 1 mm.

5. The composition of claim 4, further comprising a second flame retardant component comprising non-halogenated expandable graphite.

6. The composition of claim 4, further comprising 1 to 14 wt% of a second flame retardant component based on the total weight of the composition.

7. The composition of any one of the preceding claims, wherein the composition is configured to cure to form a foam compound that exhibits a compressive strength of at least 20 psi when measured using a Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 1 mm.

8. A composition comprising: a first component comprising an isocyanate-reactive compound and a blowing agent; a second component comprising an isocyanate compound; and At least one of the first component and the second component comprises at least 15 weight percent of the first flame retardant component based on the total weight of the composition, wherein the composition is configured to cure to form a foam compound that exhibits a compressive strength of at least 20 psi when measured using a Foam Integrity Test on a sample of the foam compound having a thickness of no greater than 1 mm.

9. The composition of claim 8, wherein the first component, the second component, the first flame retardant component, and the second flame retardant component are configured to combine to form a mixture having a viscosity of no greater than 2000 cP within 1 minute after formation when measured with a Brookfield RVF viscometer at 50 rpm using an RV-3 spindle at an ambient temperature of about 25°C.

10. The composition of claim 8, wherein the first flame retardant component exhibits a viscosity of about 10 cP to about 2000 cP at a temperature of 25°C to 35°C.

11. The composition of any one of the preceding claims, wherein the composition is configured to cure to form a foamed compound exhibiting at least one of the following: a. a flame retardancy of at least V1 as measured by the UL 94 Plastics Flammability Test when tested with a specimen of the foam compound having a thickness of not more than 1 mm, and b. At least V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a specimen of the foam compound having a thickness of not more than 1 mm.

12. The composition according to any one of the preceding claims, wherein the composition comprises at least one of: a. at least 20% by weight of the first flame retardant component based on the total weight of the composition, b. at least 25 wt % of the first flame retardant component, based on the total weight of the composition, and c. At least 30 weight percent of the first flame retardant component, based on the total weight of the composition.

13. A compound comprising: Polyurethane foam compounds, The polyurethane foam compound has a thickness of not more than 0.60 g / cm 3 The density of and Wherein the polyurethane foam compound exhibits at least V2 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a sample of the polyurethane foam compound having a thickness of not more than 1 mm.

14. The compound of claim 13, wherein the compound exhibits a compressive strength of at least 20 psi when measured using the Foam Integrity Test on a sample of the polyurethane foam compound having a thickness of no greater than 1 mm.

15. The composition of claim 13, wherein the foam composition exhibits at least one of the following: a. a flame retardancy of at least V1 as measured by the UL 94 Plastics Flammability Test when tested with a specimen of the foam compound having a thickness of not more than 1 mm, and b. At least V0 flame retardancy as measured by the UL 94 Plastics Flammability Test when tested with a specimen of the foam compound having a thickness of not more than 1 mm.